Impacto de los fenómenos climáticos en la historia de Matanzas, Cuba (1690-1876) / Impact of climatic anomalies and phenomena in the history of Matanzas city, Cuba (1690-1876) (Islas, 2021)
Este texto provee un registro de las condiciones y fenómenosclimáticos más significativos acaecidos en la región Habana-Matanzasentre 1692 y 1876. Este registro fue extraído detalladamente de documentaciónprimaria, historiográfica y meteorológica procedente de literaturacientífica moderna para establecer una relación entre los efectos climáticosy la geografía humana en el entorno de la bahía de Matanzas. Nuestroanálisis apoya que los fenómenos y anomalías climáticas jugaron un rolsignificativo en el desarrollo arquitectónico, urbanístico y socioeconómicode Matanzas desde su fundación en 1693, pero considerablemente durantela segunda mitad del siglo xviii y comienzos del xix. La integración de la climatologíaal análisis histórico nos permite acceder, aunque limitadamente,a detalles meteorológicos no registrados en los documentos, que a la vezadmiten reconstruir condiciones locales que marcaron nuestra historia.This article provides a record of noteworthy climatic eventsoccurred on the Habana-Matanzas region between 1692 and 1876. Thisrecord was extracted from detailed primary and historiographical documentation,plus meteorological data from modern climatic scientificliterature, in search of a relationship between the adverse effects ofevents such as hurricanes, ENSO events, local storms, drought andfloods on human conditions, in the area around the Matanzas Bay. Wecorroborate that climate played a significant role in the urbanistic andsocioeconomic development of Matanzas since its foundation in 1693,but more considerably during the second half of the 18th and early 19thcentury. The integration of climatology to historical research provides,although limitedly, inferences on meteorological conditions that are notavailable from document evidence, and thus allowing for generalizedreconstruction of conditions which marked local history.